2018
DOI: 10.1364/josab.35.001133
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of collimated blue-light generation in 85Rb atoms via the D1 and D2 lines

Abstract: We experimentally studied the characteristics of the collimated blue light (CBL) produced in 85 Rb vapor by two resonant laser fields exciting atoms into the 5D 3/2 state, using either the 5P 1/2 or the 5P 3/2 intermediate state. We compared the CBL output at different values of frequency detunings, powers, and polarizations of the pump lasers in these two cases, and confirmed the observed trends using a simple theoretical model. We also demonstrated that the addition of the repump laser, preventing the accumu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Nonlinear parametric and nonparametric processes in atomic media generate new optical fields with substantially different wavelengths to those used for excitation [1]. The frequency conversion of continuous wave (cw) laser light with a power of several tenths of a milliwatt into directional blue, ultraviolet and mid-infrared (IR) radiation in alkali vapours continues to be an active topic of research [2][3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Nonlinear parametric and nonparametric processes in atomic media generate new optical fields with substantially different wavelengths to those used for excitation [1]. The frequency conversion of continuous wave (cw) laser light with a power of several tenths of a milliwatt into directional blue, ultraviolet and mid-infrared (IR) radiation in alkali vapours continues to be an active topic of research [2][3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Minimization of power and atom number density thresholds of the ASE-based lasing is crucially important for possible applications for remote detection. Recently it was shown that there is an optimal power ratio between the components of the bi-chromatic beam for maximizing the efficiency of new field generation by parametric FWM [26]. A detailed study of the optimal conditions minimizing the power and atom number density thresholds is the subject of the forthcoming paper.…”
mentioning
confidence: 99%
“…Frequency up-conversion through parametric fourwave mixing has now been demonstrated in a number of environments, including near resonant cw excitation in rubidium [10][11][12][13] and cesium [14], and pulsed or cw excitation far detuned from the intermediate state [15][16][17][18]. Extensive work has been done to understand the frequency characteristics [19][20][21], observe the infrared emission [22,23], and examine competing pathways and processes [24][25][26].…”
Section: Introductionmentioning
confidence: 99%